Masculinization of betta fish (Betta sp) using cow testic flour through Artemia Immersion - Nur Insana Salam; Andi Chadijah; Rahmi; Farhana Wahyu (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2021)
Betta fish (Betta sp) is a freshwater ornamental fish during the pandemic that is very popular with the public. However, people tend to prefer male betta fish than female fish. To deal with the large number of requests, a sex reversal technique is carried out which applies hormonal engineering to change female to male sexual characters (masculinization) using natural ingredients, namely cow testicle flour. The purpose of this study was to analyze the dose of bovine testicular flour hormone on the process of oral male betta fish larvae. This research was conducted in Moncongloe Village, Maros Regency, from July to September 2021. The production of beef testicle flour was carried out in the Chemical Engineering laboratory, Ujung Pandang State Polytechnic. Betta fish seeds were kept each in an aquarium measuring 20 cm x 14 cm x 20 cm as many as 12 pieces. Soaking artemia with beef testicle flour with a predetermined dose of 60 mg L-1, 80 mg L-1 and 100 mg L-1, the duration of immersion is 24 hours. This study used a one-factor completely randomized design (CRD). The results obtained were the highest percentage of male genitalia at a dose of 100 mg L-1 with a percentage of 66.7%. The survival rate of betta fish during the maintenance period with different doses of cow testicles obtained data ranging from 80-100%.